STUDYING THE CHARACTER OF THE CHARACTERS OF THE WORK - Khaldorov Iroda Valijonovna; Makhmudova Zilola Muzaffar kizi (Zeta Repository, 2023)
This article talks about educational methods and their selection, studying and analyzing the characters of the heroes of the work.